(untitled) (Medical Forum Monthly, 2024)
Objective: To collect data of pathogens responsible for surgical site infection in elective abdominal surgeries and the drugs effective against them. Place and Duration of Study: Department of Surgery, District Head-quarters Teaching Hospital, Dera Ismail Khan from 1st January 2005 to 31st December 2009. Materials and Methods: Retrospective study on all cases of surgical site infections in elective abdominal surgeries over five years. Pus and swabs from infected wounds were sent to find the pathogens responsible for these infections and the drugs highly sensitive against them. Results: 175 cases of abdominal surgeries with surgical site infection were collected over duration of five years. Their culture sensitivity reports showed positive result in 160 cases and negative result in 15 cases. Organism most commonly responsible for abdominal wound infection in our study was Klebsiella Pneumonae. It was found in 53 patients (33.12%) followed by Pseudomonas aeriginosa in 43 patients (26.8%) and E coli in 40 patients (25%). Other micro-organisms were Staph-aurous (6.8%), Enterobactor (3.75%), Streptococcus (3.12%) and Clostridia (1.25%). Sensitivity report of these microbes showed that Sulzone (cefoperazone plus sulbactum) is the most effective antibiotic.i.e. In 90 patients (56.25%), followed by Amikacin in 40 patients (25%) and Ciprofloxacin in 15 patients (9.3%). Other drugs showing higher sensitivity against these pathogens were Fosfomycin in 10 cases (6.25%) and Imipenum in 5 cases (3.125%). Conclusion: The study gives us clues to the type of pathogens that we would expect in our surgical site infection wounds of abdominal surgery, and the antibiotics which can be empirically used against these infections.